Commercial and Instant Coffees Effectively Lower Aβ1-40 and Aβ1-42 in N2a/APPswe Cells - Zhang, Lifang; Cao, Jessica; Yang, Haiqiang; Pham, Phillip; Khan, Umer; Brown, Breanna; Wang, Yanhong; Zieneldien, Tarek; Cao, Chuanhai (Frontiers in Nutrition, 2022)
BACKGROUND: Alzheimer’s disease (AD) is a multifactorial neurological disease with neurofibrillary tangles and neuritic plaques as histopathological markers. Due to this, although AD is the leading cause of dementia worldwide, clinical AD dementia cannot be certainly diagnosed until neuropathological post-mortem evaluation. Coffee has been reported to have neurologically protective factors, particularly against AD, but coffee brand and type have not been taken into consideration in previous studies. We examined the discrepancies among popular commercial and instant coffees in limiting the development and progression through Aβ1-40 and Aβ1-42 production, and hypothesized that coffee consumption, regardless of brand or type, is beneficial for stalling the progression and development of Aβ-related AD. METHODS: Coffee samples from four commercial coffee brands and four instant coffees were purchased or prepared following given instructions and filtered for the study. 5%, 2.5%, and 1.25% concentrations of each coffee were used to treat N2a/APPswe cell lines. MTT assay was used to assess cell viability for coffee concentrations, as well as pure caffeine concentrations. Sandwich ELISA assay was used to determine Aβ concentration for Aβ1-40 and Aβ1-42 peptides of coffee-treated cells. RESULTS: Caffeine concentrations were significantly varied among all coffees (DC vs MDC, PC, SB, NIN, MIN p<0.05). There was no correlation between caffeine concentration and cell toxicity among brands and types of coffee, with no toxicity at 0.5mg/ml caffeine and lower. Most coffees were toxic to N2a/APPswe cells at 5% (p<0.05), but not at 2.5%. Most coffees at a 2.5% concentration reduced Aβ1-40 and Aβ1-42 production, with comparable results between commercial and instant coffees. CONCLUSION: All coffees tested have beneficial health effects for AD through lowering Aβ1-40 and Aβ1-42 production, with Dunkin' Donuts® medium roast coffee demonstrating the most consistent and optimal cell survival rates and Aβ concentration. On the other hand, Starbucks® coffee exhibited the highest cell toxicity rates among the tested coffees.